Distinct modes of vertebrate hypaxial muscle formation contribute to the teleost body wall musculature - Windner, SE (2011)
The formation of the body wall musculature in vertebrates is assumed to be initiated by direct ventral extension of the somites/myotomes. This contrasts to the formation of limb muscles and muscles involved in feeding or respiration/ventilation, which are founded by migratory muscle precursors (MMPs) distant to the somites. Here, we present evidence from morphology and expression of molecular markers proposing that the formation of the two muscle layers of the teleost body wall involves both of the above mechanisms: (i) MMPs from somites 5 and 6 found an independent muscle primordium (posterior hypaxial muscle, PHM) which subsequently gives rise to the most anterior two segments of the medial obliquus inferioris (OI) muscle. (ii) Direct epithelial extension of the hypaxial myotomes generates the OI segments from somite 7 caudalward and the entire lateral obliquus superioris (OS) muscle. The findings are discussed in relation to the evolution of hypaxial myogenic patterning including functional considerations. We hypothesize that the potential of the most anterior somites to generate migratory muscle precursors is a general vertebrate feature that has been differently utilised in the evolution in vertebrate groups.